PELATIHAN EKSTRAKURIKULER TARI KREASI DALAM MEMBENTUK SIKAP PERCAYA DIRI SISWA OLEH KAMPUS MENGAJAR 7 DI SDN 50 CAKRANEGARA - ayunia, Nadia; Yulia Rezqiani (Al-mujahidah, 2024)
Abstrct. Extracurricular dance is a very important activity to build students' self-confidence and sense of responsibility at the 50 Cakranegara State Elementary School. With extracurricular activities, they are able to express themselves through dance movements and musical rhythms so that students' self-confidence can develop. The research method used is the PALS approach (Paraticcipatory action learning system). The data collection was obtained based on observations in grades 4 and 5 as well as notes while in the field. The results of the research showed that children in grades 4 and 5 who took part in dance extracurricular activities and received dance instruction appeared to have a confident attitude. This is demonstrated by several factors, including responsibility and self-confidence. Aspect of self-confidence: students who are always confident and self-confident seem to have a firm stance, drive and joy, which can be seen in every action they take. The ability to fulfill obligations and fulfill commitments is a measure of responsibility. With this creative dance extracurricular, it is hoped that it can foster two aspects, namely confidence in one's abilities and responsibility. Key Word. Extracurricular, Confidence, Dance Art